Design, Fabrication, and Performance Analysis of an Automatic Horizontal Egg Incubator - Yadav, Bharosh Kumar; Pokhrel, Nischal; Khatiwada, Dinesh; Khanal, Madan; Bajracharya, Triratna; Dhakal, Rabin (Journal of the Institute of Engineering, 2021)
This research paper presents the design, construction, and performance testing of an automatic electrically powered egg incubator utilizing the horizontal placement of eggs. This experimental research was driven by the specific design and construction of a well-insulated rectangular egg-incubating box of dimension 400 mm × 600 mm × 500 mm and thickness 30 mm, where sample eggs were kept for experimental test analysis under the favorable temperature and humidity inside the box, which was automatically controlled. The device was made to operate under the temperature range of 37°C – 38°C, which was found to be adequate for developing embryos and also maintaining relative humidity at the range of 45–60% for the first 18 days and 60–90% for the last three days. Finally, in this machine, the egg tray was adjusted horizontally, and a motor clamped mechanism was used 5 times a day which was controlled automatically by a micro-controller for the motion of eggs up to 18 days of incubation. In conclusion, this egg-incubating machine has an efficiency and hatchability of 72.22%.